A chromosome-scale genome assembly of Isatis indigotica, an important medicinal plant used in traditional Chinese medicine: An Isatis genome. (1st February 2020) - Kang, Minghui; Wu, Haolin; Yang, Qiao; Huang, Li; Hu, Quanjun; Ma, Tao; Li, Zaiyun; Liu, Jianquan
Abstract: Isatis indigotica (2 n = 14) is an important medicinal plant in China. Its dried leaves and roots (called Isatidis Folium and Isatidis Radix, respectively) are broadly used in traditional Chinese medicine for curing diseases caused by bacteria and viruses such as influenza and viral pneumonia. Various classes of compounds isolated from this species have been identified as effective ingredients. Previous studies based on transcriptomes revealed only a few candidate genes for the biosynthesis of these active compounds in this medicinal plant. Here, we report a high-quality chromosome-scale genome assembly of I . indigotica with a total size of 293.88 Mb and scaffold N50 = 36.16 Mb using single-molecule real-time long reads and high-throughput chromosome conformation capture techniques. We annotated 30, 323 high-confidence protein-coding genes. Based on homolog searching and functional annotations, we identified many candidate genes involved in the biosynthesis of main active components such as indoles, terpenoids, and phenylpropanoids. In addition, we found that some key enzyme-coding gene families related to the biosynthesis of these components were expanded due to tandem duplications, which likely drove the production of these major active compounds and explained why I. indigotica has excellent antibacterial and antiviral activities. Our results highlighted the importance of genome sequencing in identifying candidate genes for metabolite synthesis in medicinal plants.